The Organisation of Knowledge in Virtual Libraries in the Field of Education - Hudon, Michèle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
In this paper, we propose to discuss the results of a research project which focuses on Web resources in the field of education. The project and the paper relate to the second theme of this year's conference: How are discourse communities and fields of knowledge redefining themselves in changing technological contexts? Education is a culturally and politically stamped field of knowledge and practice. Education objectives, methods and systems...